A COMPARATIVE ANALYSIS OF SUBCLINICAL HYPOTHYROIDISM IN INDIVIDUALS WITH METABOLIC SYNDROME VERSUS THOSE WITHOUT METABOLIC SYNDROME: A CROSS-SECTIONAL STUDY. - Adnan Imam; Prashant Dharepgol (Student's Journal of Health Research Africa, 2023)
Aim: The objective is to compare the thyroid status of people with metabolic syndrome (MetS) to that of healthy controls.